Comparative Pushover Analysis of Multistory Buildings with Concrete-Filled and Non-Filled Double Channel Section with Battening Columns - Kadariya, Supal; Ghimire, Saideep; Paudel, Saurav; Nepal, Sudarshan; Gautam, Sarthak (NPRC Journal of Multidisciplinary Research, 2025)
Background: The seismic performance of steel columns is critical in earthquake-prone regions, where conventional non-filled battened double channel sections often exhibit limited lateral stiffness and ductility. Recent earthquakes, such as the 2015 Gorkha earthquake, have highlighted vulnerabilities in steel structures due to insufficient energy dissipation. Concrete-filled battened double channel columns (CFC) offer a promising solution by combining the strength of steel and the stiffness of concrete, enhancing seismic resilience. Objective: This study conducts a comparative pushover analysis of multistory buildings with concrete-filled (CFC) and non-filled battened double channel columns to evaluate their seismic performance. Key parameters include base shear capacity, roof displacement, ductility ratio, energy dissipation, and post-peak softening behavior. Methods: A G+7 residential building was modeled in SAP2000 with identical geometry and loading conditions for both column types. Nonlinear static pushover analysis was performed under displacement-controlled loading, with plastic hinges assigned per FEMA-356 guidelines. The models were compared based on seismic performance indicators, including capacity curves, hinge formation, and performance points. Findings: The CFC model achieved 24% higher base shear (19,230 kN vs. 15,560 kN) and greater roof displacement (446 mm vs. 402 mm). Ductility ratio improved by 12.7% (3.38 vs. 3.0) in the CFC model. Energy dissipation increased by 31.8%, with a more gradual post-peak softening response. Plastic hinge distribution showed that the CFC model exhibited better inelastic deformation capacity before collapse. Conclusion: Concrete-filled battened double channel columns significantly enhance lateral strength, ductility, and energy dissipation compared to non-filled sections. However, higher displacement demands must be considered in design. Future work should incorporate nonlinear dynamic time-history analysis for a more comprehensive assessment. The findings support revising seismic design codes (e.g., NBC 105:2020, AISC 360) to include provisions for composite open-section columns.